Human β-Defensins in Diagnosis of Head and Neck Cancers - Kompuinen Jenna; Keskin Mutlu; Yilmaz Dogukan; Gürsoy Mervi; Gürsoy Ulvi Kahraman (Switzerland, 2025)
Head and neck cancers are malignant growths with high death rates, which makes the early diagnosis of the affected patients of utmost importance. Over 90% of oral cavity cancers come from squamous cells, and the tongue, oral cavity, and salivary glands are the most common locations for oral squamous cell carcinoma lesions. Human β-defensins (hBDs), which are mainly produced by epithelial cells, are cationic peptides with a wide antimicrobial spectrum. In addition to their role in antimicrobial defense, these peptides also take part in the regulation of the immune response. Recent studies produced evidence that these small antimicrobial peptides are related to the gene and protein expression profiles of tumors. While the suppression of hBDs is a common finding in head and neck cancer studies, opposite findings were also presented. In the present narrative review, the aim will be to discuss the changes in the hBD expression profile during the onset and progression of head and neck cancers. The final aim will be to discuss the use of hBDs as diagnostic markers of head and neck cancers.